Analiza akterjev ukrajinsko-ruske vojne: po dveh letih in pol (februar 2022- julij 2024) - Ružičič Červek, Luka (Sodobni vojaški izzivi, 2024)
The Russo-Ukrainian War was the first major conflict in Europe since the Balkan Wars. The conflict has been ongoing since 2014 with the annexation of Crimea. Russia expected a quick and easy victory and the subjugation of Ukraine in its February 2022 attack. Russian forces encountered fierce resistance from the Ukrainian army and civilian population. Russian troops were forced to reorganise and focus on the southeastern part of Ukraine. The aggression was met with a solid international response and condemnation, and many countries imposed sanctions against Russia. Western countries, led by the USA and the EU, supported Ukraine with extensive humanitarian and military assistance. The article analyses the conflict using the Birmingham method and focuses on the key actors. The conclusion summarises the analysis of the possibility of ending the conflict and provides strategic reflection.
Keywords: denuklearizacija; mednarodni konflikti; mednarodni odnosi; oboroženi konflikti; Rusija; rusko-ukrajinska vojna; Ukrajina; vojni konflikti